THE RELATIONSHIP OF MOTHER'S BEHAVIOR ABOUT BOTTLE MILK FEEDING WITH CARIES LEADING IN SCHOOL - Reca; Cut Aja Nuraskin; Teuku Salfiyadi; Mufizarni (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Rampant caries is a multifactorial disease that interacts with each other. Factors in the incidence of dental caries include factors from food, oral hygiene, and habits that are not in accordance with health such as eating food and feeding through bottles. In addition, parents' misunderstanding of the causes of caries, such as using milk, further exacerbates the occurrence of rampant caries in children. This study aims to determine the relationship between mother's behavior regarding bottle feeding with rampant caries in TK Negeri 7 Sabang City. This research is analytic with cross-sectional approach. Sampling used total sampling, namely all 45 children of TK Negeri 7 Sabang City and their mothers as respondents, by conducting dental examinations on children and interviews with mothers. The research instrument used a diagnostic set and a questionnaire. The results of the study were tested statistically using the SPSS program with a chi-square test (a = 0.05). It can be concluded that there is a relationship between mother's behavior about bottle feeding and rampant caries in TK Negeri 7 Sabang City. It is recommended to further improve good behavior towards children when giving bottle milk to avoid rampant caries.